The decline of smoking initiation among Aboriginal and Torres Strait Islander secondary students: implications for future policy. (10th August 2020) - Heris, Christina L.; Guerin, Nicola; Thomas, David P.; Eades, Sandra J.; Chamberlain, Catherine; White, Victoria M.
Abstract: Objective : Smoking is a major cause of preventable illness for Aboriginal and Torres Strait Islander people, with most commencing in adolescence. Understanding trends in youth tobacco use can inform prevention policies and programs. Methods : Logistic regression models examined smoking trends among Aboriginal and Torres Strait Islander and all students aged 12–17 years, in five nationally representative triennial surveys, 2005–2017. Outcomes measured lifetime, past month, past week tobacco use and number of cigarettes smoked daily (smoking intensity). Results : Aboriginal and Torres Strait Islander students' never smoking increased (2005: 49%, 2017: 70%) with corresponding declines in past month and week smoking. Smoking intensity reduced among current smokers (low intensity increased 2005: 67%, 2017: 77%). Trends over time were similar for Aboriginal and Torres Strait Islander students as for all students (8‐10% annual increase in never smoking). Conclusions : Most Aboriginal and Torres Strait Islander students are now never smokers. Comparable declines indicate similar policy impact for Aboriginal and Torres Strait Islander and all students. Implications for Public Health : Comprehensive population‐based tobacco control policies can impact all students. Continued investment, including in communities, is needed to maintain and accelerate reductions among Aboriginal and Torres Strait Islander students to achieve equivalent prevalence rates and reduce health inequities.